Bowel function and transit rate during the menstrual cycle. Issue 5 (May 1989) - Kamm, M A; Farthing, M J; Lennard-Jones, J E
Abstract : The whole gut transit rate has been measured in the follicular and luteal phases of the menstrual cycle in 18 healthy women in whom ovulation was confirmed biochemically. Mean transit time in the follicular phase (45.2 (2.7) h, mean (SEM) was not significantly different from the luteal phase (51.3 (4.1], p = 0.12. Stool weight was also not significantly different in the two phases (132 (7) v 123 (10) g/day). A diary card kept for the entire menstrual cycle revealed no change in bowel frequency or stool consistency during the menstrual, follicular or luteal phases. Under normal physiological conditions the sex hormones do not have a major effect on bowel function.